Research on Leakage Monitoring and Identification of Buried Pipeline for Finished Oil Products - Gongxing LI (Shiyou huagong gaodeng xuexiao xuebao, 2025)
Leakage of refined oil pipeline can cause environmental pollution and threaten the safety of residents' lives and properties, making leakage monitoring and identification critical. This study establishes a leakage monitoring and identification model for undulating buried pipelines, generates pressure waves by controlling valve openings, and monitors and identifies leakage locations. The effects of valve opening and valve opening/closing interval time on leakage localization accuracy were analyzed. Results show that the model exhibits high accuracy for identifying medium⁃sized hole leaks but lower prediction capabilities for small and large holes, resulting in larger relative errors in leakage localization. When the valve opening decreases from 90% to 10%, 30%, and 50%, the amplitude of pressure wave signals decreases, and the relative error in leakage localization calculated by the model gradually increases. A valve opening of 10% is recommended. As the valve opening/closing interval time increases, the relative error in leakage localization grows due to interactions between pressure wave signals and reflected signals, with an optimal interval time of 1 second recommended.